ADJUBIL: A phase II study of immunotherapy with durvalumab and tremelimumab in combination with capecitabine or without capecitabine in adjuvant situation for biliary tract cancer - Eickhoff, Regina; Pons, Miriam; Kochen, Lisa; Vortmeyer, Doerthe; Al-Batran, Salah-Eddin; Habibzade, Timursah; Adler, Marius; Gonzalez-Carmona, Maria A; Ettrich, Thomas Jens; Koehne, Claus-Henning; Pink, Daniel; van Boemmel, Florian; et al. (Journal of clinical oncology, 2024)
TPS583Background: Despite improvements in multidisciplinary healthcare, patients with biliary tract cancer (BTC) have a poor outcome and effective treatment options are limited. Only 20 % of patients are eligible for surgical resection with curative intent, with 5-year overall survival rates < 10 % for all patients. Data on adjuvant chemotherapy alone for BTC are conflicting, and the SOC is treatment with capecitabine according to the UK BILCAP trial, even though BILCAP was formally negative. Based on the positive data for durvalumab in the TOPAZ-1 trial in BTC and for the STRIDE regimen in HCC according to the Himalaya trial data, the evaluation of the IO combination in the adjuvant setting seems promising. Also, the MediTreme trial showed promising response rates in BTC. Preclinical studies indicate that the antibody combination leads to stronger and more durable anti-tumour effects than single therapies, as it synergistically modulates the tumour's immunosuppressive microenvironment, which is particularly pronounced in cholangiocarcinoma. The aim of the ADJUBIL trial is to evaluate the clinical activity of the anti-PD-L1 (programmed-death 1 ligand) antibody durvalumab and the anti-CTLA-4 (cytotoxic T- lymphocyte-associated antigen 4) antibody tremelimumab in combination with or without capecitabine in patients with respectable BTC in the adjuvant setting. This is a randomized phase II study with a pick-the-winner design. The winner of ADJUBIL could be tested against the current SOC capecitabine in a subsequent phase 2/3 trial. Methods: The ADJUBIL trial is an open-label, multicenter phase II study, including patients with BTC after curative surgery (R0/R1) with no previous systemic treatment. Patients are randomized (1:1) to receive either tremelimumab (300 mg, one dose on C1D1) plus durvalumab (1500 mg every 4 weeks; max. 12 months), with or without capecitabine (1250 mg/m2 twice a day on day 1-14 of 3-weekly cycles; max. 8 cycles). 40 evaluable patients will be enrolled in the study to receive anticancer treatment until disease recurrence or intolerable toxicities. Primary objective is to assess the anti-tumor activity of the treatment in both arms by the recurrence-free survival rate after 12 months. Secondary endpoints are recurrence-free survival, overall survival, toxicity, and quality of life. Exploratory endpoints are to identify predictive biomarkers for recurrence-free survival and overall survival. Study start of the ADJUBIL trial was in June 2021. By September 2023, 15 centers in Germany have been activated and 23 out of 40 planned patients have been enrolled. The first 5 patients in each arm were subject to a safety lead-in phase with close monitoring of (serious) adverse events. The safety assessment revealed no concerns. The study is ongoing. Clinical trial information: NCT05239169.